Aqueous-solution-driven HfGdOx gate dielectrics for low-voltage-operated α-InGaZnO transistors and inverter circuits. (1st August 2020) - Zhang, Yongchun; He, Gang; Wang, Wenhao; Yang, Bing; Zhang, Chong; Xia, Yufeng
Abstract: In this work, a non-toxic and environmentally friendly aqueous-solution-based method has been adopted to prepare gadolinium-doped hafnium oxide (HfO2 ) gate dielectric thin films. By adjusting the gadolinium (Gd) doping concentration, the oxygen vacancy content, band offset, interface trap density, and dielectric constant of HfGdO x (HGO) thin films have been optimized. Results have confirmed that HGO thin films with Gd doping ratio of 15 at.% have demonstrated appropriate dielectric constant of 27.1 and lower leakage current density of 5.8 × 10 −9 A cm -2 . Amorphous indium-gallium-zinc oxide (α-IGZO) thin film transistors (TFTs) based on HGO thin film (Gd: 15 at.%) as gate dielectric layer have exhibited excellent electrical performance, such as larger saturated carrier mobility ( μ sat ) of 20.1 cm 2 V -1 S -1, high on/off current ratio ( I on / I off ) of ∼10 8, smaller sub-threshold swing (SS) of 0.07 V decade -1, and a negligible threshold voltage shift (△ V TH ) of 0.08 V under positive bias stress (PBS) for 7200 s. To confirm its potential application in logic circuit, a resistor-loaded inverter based on HGO/α-IGZO TFTs has been constructed. A high voltage gain of 19.8 and stable full swing characteristics have been detected. As a result, it can be concluded that aqueous-solution-driven HGO dielectrics have potential application in high resolution flat panel displays and ultra-large-scale integrated logic circuits.